Innate Immune Interactions between Bacillus anthracis and Host Neutrophils - Liu, Janet Z.; Ali, Syed R.; Bier, Ethan; Nizet, Victor (Frontiers in Cellular and Infection Microbiology, 2018)
Bacillus anthracis, the causative agent of anthrax, has been a focus of study in host-pathogen dynamics since the 19th century. While the interaction between anthrax and host macrophages has been extensively modeled, comparatively little is known about the effect of anthrax on the immune function of neutrophils, a key frontline effector of innate immune defense. Here we showed that depletion of neutrophils significantly enhanced mortality in a systemic model of anthrax infection in mice. Ex vivo, we found that freshly isolated human neutrophils can rapidly kill anthrax, with specific inhibitor studies showing that phagocytosis and reactive oxygen species (ROS) generation contribute to this efficient bacterial clearance. Anthrax toxins, comprising lethal toxin (LT) and edema toxin (ET), are known to have major roles in B. anthracis macrophage resistance and systemic toxicity. Employing isogenic wild-type and mutant toxin-deficient B. anthracis strains, we show that despite previous studies that reported inhibition of neutrophil function by purified LT or ET, endogenous production of these toxins by live vegetative B. anthracis failed to alter key neutrophil functions. The lack of alteration in neutrophil function is accompanied by rapid killing of B. anthracis by neutrophils, regardless of the bacteria’s expression of anthrax toxins. Lastly, our study demonstrates for the first time that anthrax induced neutrophil extracellular trap (NET) formation.